2020
DOI: 10.3389/fnins.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Workload Indicators During Teleoperation of an Unmanned Aerial Vehicle Shepherding a Swarm of Unmanned Ground Vehicles in Contested Environments

Abstract: Background: Although many electroencephalographic (EEG) indicators have been proposed in the literature, it is unclear which of the power bands and various indices are best as indicators of mental workload. Spectral powers (Theta, Alpha, and Beta) and ratios (Beta/(Alpha + Theta), Theta/Alpha, Theta/Beta) were identified in the literature as prominent indicators of cognitive workload. Objective: The aim of the present study is to identify a set of EEG indicators that can be used for the objective assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 68 publications
1
30
0
1
Order By: Relevance
“…Additionally, in previous WM studies, θ -frequency range activity was reported to be linked to WM load and task difficulty [ 57 , 65 67 ]. Some studies also found a linear increase of FMT power with load only in the high-WM capacity group [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, in previous WM studies, θ -frequency range activity was reported to be linked to WM load and task difficulty [ 57 , 65 67 ]. Some studies also found a linear increase of FMT power with load only in the high-WM capacity group [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 97%
“…A sender that changes its states faster than a recipient's ability to receive and decode the messages needs to be more predictable to the recipient to compensate for the uncertainty caused by latency [14]. Moreover, previous research has demonstrated that latency increases human cognitive load [52].…”
Section: Communicationmentioning
confidence: 99%
“…To measure depth reasoning, we recorded Electroencephalography (EEG) from participants while they were performing a tacit coordination game. From the EEG, we have extracted an electrophysiological index, the Theta-Beta Ratio (TBR), which are frequency bands that provide an index of oscillatory activity associated with cognitive load [31][32][33]. The TBR enabled us to examine whether there is a correlation between coordination ability and cognitive load.…”
Section: Introductionmentioning
confidence: 99%